Pertumbuhan dan Produksi 3 Jenis Leguminosa Pohon di Pertanaman Kelapa Pasca Defoliasi - Mohammad Takdir; Wardi Wardi; Andi Baso Lompengen Ishak (Politeknik Negeri Jember, 2019)
This research aimed to find out the growth and production of indigofera, lamtoro, and kaliandra in coconut plantations after defoliation. The study was conducted in Bulubete Village, South Dolo Subdistrict, Sigi Regency, Central Sulawesi. This study was conducted on 3 types of legumes, namely indigofera (Indigofera sp.), lamtoro (Leucaena leucocephala), and calliandra (Calliandra calothyrsus). Variables observed were plants height (TT) and fresh production yields (PS) on 30, 60, and 90 days. The results of data were analyzed descriptively. The results showed the average of fresh legumes production were harvested at the age of 90 days in 3 types of legumes: indigofera, lamtoro, and calliandra was 0.96 kg; 0.37 kg; 0.63 kg; and post fertilization reaches 5.50 to 7.66 kg; 0.78 to 2.22 kg; and 2.0 to 3.28 kg. It was concluded that the introduction of three legumes under coconut stands that were very adaptive was indogofera. This can be used as an alternative solution for the limitations of forage in te small farms.Â